An Eco-friendly Method for Synthesis of Symmetrical and Unsymmetrical Benzoin Derivatives - Safari, Javad; Moshtael Arani, Naimeh; Ramezan Isfahani, Anousheh (Asian Journal of Chemistry, 2010)
A rapid, highly efficient and mild green synthesis of symmetrical and unsymmetrical benzoin derivatives was achieved from the reaction of benzaldehyde derivatives with potassium cyanide in dimethyl sulfoxide under argon gas and ultrasound. This simple method affords benzoin derivatives at room temperature in short reaction times with high yield and purity.